Role of functional pharmacological therapy in post-stroke depression: a narrative review - Corallo, Francesco (J Int Med Res, 2020)
OBJECTIVE: We conducted a narrative review to investigate whether antidepressant therapy, including the use of selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors (SNRIs) or the use of supportive drugs (i.e., citicoline or choline alfoscerate) as a substitute for antidepressant therapy, reduces depression in patients with cerebrovascular diseases. METHODS: A systematic search of the PubMed and Web of Science databases was performed, including review articles and other studies to identify additional citations. Only 4 of 1566 publications met the inclusion/exclusion criteria and were selected. RESULTS: Studies showed that post-stroke depression (PSD) could be treated with antidepressant therapy, as well as supportive drugs such as citicoline or choline alfoscerate, which may have antidepressant effects. CONCLUSIONS: The findings support the efficacy of citicoline as a treatment for depression. Studies aimed to discover the characteristics of these psychostimulants in relation to PSD treatment should be performed.